LHC main dipole magnet circuits : sustaining near-nominal beam energies - Rowan, Scott M (University of Glasgow, 2016)
Crossing the Franco-Swiss border, the Large Hadron Collider (LHC), designed to collide 7 TeV proton beams, is the world's largest and most powerful particle accelerator the operation of which was originally intended to commence in 2008. Unfortunately, due to an interconnect discontinuity in one of the main dipole circuit's 13 kA superconducting busbars, a catastrophic quench event occurred during initial magnet training, causing significant physical system damage. Furthermore, investigation into the cause found that such discontinuities were not only present in the circuit in question, but throughout the entire LHC. This prevented further magnet training and ultimately resulted in the maximum sustainable beam energy being limited to approximately half that of the design nominal, 3.5-4 TeV, for the first three years of operation (Run 1, 2009-2012) and a major consolidation campaign being scheduled for the first long shutdown (LS 1, 2012-2014). Throughout Run 1, a series of studies attempted to predict the amount of post-installation training quenches still required to qualify each circuit to nominal-energy current levels. With predictions in excess of 80 quenches (each having a recovery time of 8-12+ hours) just to achieve 6.5 TeV and close to 1000 quenches for 7 TeV, it was decided that for Run 2, all systems be at least qualified for 6.5 TeV operation. However, even with all interconnect discontinuities scheduled to be repaired during LS 1, numerous other concerns regarding circuit stability arose. In particular, observations of an erratic behaviour of magnet bypass diodes and the degradation of other potentially weak busbar sections, as well as observations of seemingly random millisecond spikes in beam losses, known as unidentified falling object (UFO) events, which, if persist at 6.5 TeV, may eventually deposit sufficient energy to quench adjacent magnets. In light of the above, the thesis hypothesis states that, even with the observed issues, the LHC main dipole circuits can safely support and sustain near-nominal proton beam energies of at least 6.5 TeV. Research into minimising the risk of magnet training led to the development and implementation of a new qualification method, capable of providing conclusive evidence that all aspects of all circuits, other than the magnets and their internal joints, can safely withstand a quench event at near-nominal current levels, allowing for magnet training to be carried out both systematically and without risk. This method has become known as the Copper Stabiliser Continuity Measurement (CSCM). Results were a success, with all circuits eventually being subject to a full current decay from 6.5 TeV equivalent current levels, with no measurable damage occurring. Research into UFO events led to the development of a numerical model capable of simulating typical UFO events, reproducing entire Run 1 measured event data sets and extrapolating to 6.5 TeV, predicting the likelihood of UFO-induced magnet quenches. Results provided interesting insights into the involved phenomena as well as confirming the possibility of UFO-induced magnet quenches. The model was also capable of predicting that such events, if left unaccounted for, are likely to be commonplace or not, resulting in significant long-term issues for 6.5+ TeV operation. Addressing the thesis hypothesis, the following written works detail the development and results of all CSCM qualification tests and subsequent magnet training as well as the development and simulation results of both 4 TeV and 6.5 TeV UFO event modelling. The thesis concludes, post-LS 1, with the LHC successfully sustaining 6.5 TeV proton beams, but with UFO events, as predicted, resulting in otherwise uninitiated magnet quenches and being at the forefront of system availability issues.